Fabrication life prediction model for HDPE/Cr2O3 composites toward roof passive cooling - Tiankai, Jiang; Jun, Zhang; Wei, Huang; Keda, Zhu (Construction & building materials, 2023)
[Display omitted] •The composites can be used as roof due to the visual effect and cooling performance.•The innovative addition of Cr2O3 skillfully combines the visual effect, solar reflection and UV resistance.•A new method of failure point selection is proposed.•Using mathematical model to predict service life.•The composites can be used for more than 15 years. Passive cooling materials have been widely investigated to reduce building energy consumption. However, references about life prediction of the materials are insufficient. In this work, a novel life prediction model based on the passive cooling composites was established. The inorganic pigment chromium oxide (Cr2O3) was introduced into the high density polyethylene (HDPE) matrix to prepare HDPE/Cr2O3 composites with high long wave infrared (LWIR) emissivity and near infrared (NIR) reflectivity. The composites showed excellent cooling performance and color stability. The addition of ultraviolet absorber (UVA) and hindered amine light stabilizer (HALS) further improved the UV resistance of HDPE/Cr2O3 composites. HALS performs better and meets the needs of long-life outdoor use. Furthermore, a new failure point selection method is proposed and a model is established to predict the actual service life of HDPE/Cr2O3 composites, which provides theoretical guidance for the outdoor long-life use of the polymer composites. Based on the model, the fabricated HDPE/Cr2O3/HALS system can be used for more than 15 years. The long-term cooling composites can be used for building roof and wall to effectively reduce the indoor temperature and realize the sustainable use of energy. Besides, if used in military engineering, it has excellent cooling function and military camouflage effect. In addition, the composites can also be widely used in outdoor decoration, artificial lawn, floating materials and other fields.